Leucocalocybe mongolica inoculation enhances rice growth by reallocating resources from flavonoid defense to development via MYB/bHLH/WRKY networks - Duan, Mingzheng; Wang, Mei; Wei, Fuhan; Han, Sirui; He, Zhifang; Hu, Dong; Ran, Qiuyue; Duan, Xiande; Yang, Shunqiang; Rao, Muhammad Junaid (Frontiers in Plant Science, 2025)
The relationship between plants and beneficial fungi offers a sustainable approach to enhance crop productivity and stress resilience. This study investigated the effects of Leucocalocybe mongolica strain LY9 on rice (Oryza sativa L.) growth, flavonoid metabolism, and transcriptional regulation. Rice plants treated with varying concentrations of LY9-transformed soil (10%, 30%, and 50%) exhibited significant improvements in phenotypic traits, including increased tiller numbers, shoot length (989 mm), and root length (518 mm), alongside elevated chlorophyll content, indicating enhanced photosynthetic efficiency. However, total flavonoid content decreased at the highest LY9 concentration, suggesting a metabolic trade-off between growth promotion and secondary metabolite production. Transcriptomic analysis revealed dose-dependent modulation of MYB, bHLH, and WRKY transcription factor genes such as Os04g0605100-WRKY68 and Os05g0553400-R2R3MYB84, while metabolomic profiling identified selective upregulation of stress-responsive flavonoids, such as chalcones (e.g., 2’,4’-dihydroxy-2,3’,6’-trimethoxychalcone and naringenin chalcone) and isoflavones (e.g., prunetin), while flavones were predominantly suppressed. Pearson correlation analyses underscored negative associations between flavonoid levels and growth traits, highlighting LY9’s role in reallocating resources from defense to growth. These findings demonstrate that LY9 enhances rice productivity by modulating flavonoid metabolism and transcriptional networks, offering insights into sustainable agricultural practices for stress resilience. Additionally, the study underscores the potential of LY9 as a biofertilizer to optimize rice growth while maintaining stress resilience through targeted metabolic adjustments.